PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 10 SUNGAI SAPIH KOTA PADANG - Yen Gusmaneli; Pebriyenni Pebriyenni; Yulfia Nora (Cerdas Proklamator, 2020)
This study aims to determine the effect of cooperative learning model type Make A Match on student learning outcomes on learning IPS. The type of this research is experimental research. The population in this study is all students of class IV SD Negeri 10 Sungai Sapih Padang, amounting to 167 people. The sample in this research is the students of class IVB As the experimental class and the class IVC As the control class that the way of sampling using random sampling. The data collected in the form of students' IPS learning outcomes. Data collection techniques in this study using the test. The test he used was an objective test. Data obtained from statistical test. The result of the research on the students' IPS test result showed the average score of IPS learning result in the experimental class that is 84.24 and the control class is 75.74. Hypothesis testing using t-test shows thitung> ttable, with tcount equal to 3,56 and ttable value equal to 2 at significant level 0,05. Based on the result of this research can be concluded that there is influence of learning result of IPS student of experiment class by using make learning model Make A Match